Effect of a New Prestrain, Intercritical Annealing, Quenching, and Partitioning Process on the Microstructure and Mechanical Properties of Medium‐Manganese Steels. Issue 11 (28th September 2022) - Wu, Zhonglin; Jing, Cainian; Feng, Yan; Li, Zhaotong; Lin, Tao; Zhao, Jingrui
Abstract : A new process combining 4% prestrain, intercritical annealing, quenching, and partitioning (prestrain–IA–Q&P) is used to investigate the effect of tensile number on the microstructure and mechanical properties of medium‐manganese steels. A microstructural model is built based on the specimens' microstructure and mechanical properties. The amount of tiny brilliant white carbide particles precipitated in the microstructure seems to grow with the number of stretches. The test steel's tensile strength first decreases and then increases. However, the product of tensile strength and elongation exhibits the opposite trend. The new process improves test steel elongation compared with IA–Q&P. This might be because multiple stretches have destroyed the original microstructure of the test steel. Consequently, the test steel generated more deformation bands and dislocation energy. Simultaneously, grain refinement and carbide precipitation in the test steel increase the nucleation point of austenite, resulting in a diffuse distribution of the retained austenite. The tested steel is stretched numerous times, enhancing the capacity of the microstructure's ferrite/martensite/retained austenite to accept dislocations, and there is increased dislocation slip and back stress production between the microstructures. As a result, test steel's ductility is increased by the transformation induced plasticity effect of retained austenite and the synergistic deformation of ferrite. Abstract : This research, it is offered a new prestrain–intercritical annealing–quenching and partitioning (IA–Q&P) process in which the test steel is first prestrained and then subjected to IA–Q&P heat treatment. The new process's impact on the microstructure and properties of the test steel is researched, and a microstructure model is built. The process greatly improves the plastic toughness of the test steel.